Hidradenitis suppurativa: A comparison of guidelines - Verena Isak; Steve R Feldman; Rita O Pichardo (Wolters Kluwer Medknow Publications, 2018)
Hidradenitis suppurativa (HS) is a chronic inflammatory disease of the folliculopilosebaceous unit (FPSU) in the intertriginous skin areas, especially axilla, groin, perineum, and peri- or sub-mammary fold in women, with secondary inflammation of eccrine and apocrine glands. HS disease activity and severity can be divided into three different stages according to the Hurley staging system. Stage I disease consists of single or multiple abscesses, while in Stage II, additional sinus tract formation or scarring can be seen, and in Stage III, interconnected tracts and abscesses have developed over a complete anatomic area. Due to its high disease burden, the extent to which HS negatively impacts patients' quality of life is higher than that of most other chronic dermatological conditions. Pain is considered one of the worst aspects of HS. In this article, we compare different guidelines for the management of HS between hospitals in Europe and the U.S. for Hurley Stage I, II, and III. Existing treatment guidelines were identified through systematic review of medical databases, including PubMed, using the search terms "hidradenitis suppurativa treatment guidelines" as well as "acne inversa treatment guidelines" for the European and German treatment guidelines, as well as American hospital-specific treatment algorithms, including Henry Ford Hospital, Detroit, Michigan, and Mayo Clinic, Rochester, Minnesota. In the German S1 guidelines, the goal is an improvement of one Hurley stage and/or a 25% improvement of the Sartorius score or the dermatology life quality index within 12 weeks. Radical surgical or laser excision, oral combination therapy of clindamycin and rifampin, or alternatively tetracycline, topical clindamycin, and hormonal therapy are recommended, while topical resorcinol, dapsone, finasteride, zinc gluconate, and acitretin are the treatment options that can be taken into consideration. Unlike the European or German S1 guidelines or the algorithm proposed by the Henry Ford Hospital, more systemic antibiotic therapy options are suggested in the Mayo Clinic algorithm before the addition of immunosuppressive therapy. Evaluation for efficacy happens every 3 months, and in case of treatment failure, the antibiotic regimen is changed and reevaluated 3 months later. Options include Trimethoprim-sulfamethoxazole, amoxicillin-clavulanate, fluoroquinolones, clindamycin, and rifampin, as well as rifampin plus moxifloxacin plus metronidazole. If none of the proposed antibiotic therapies help, acitretin, dapsone, or cyclosporine may be used instead. In refractory HS, infliximab or adalimumab is added to the regimen. For Stage III disease or in case of treatment failure so far, wide local excision as an addition to medical therapies can be considered. With the literature of the existing treatment options mostly being low evidence, scarce new randomized controlled trials, and the existing guidelines leaving room to interpretation, a gold standard for the treatment of HS does not yet exist. Further large-scale, randomized studies are necessary to continue treatment exploration and improve treatment regimens.